2017
DOI: 10.1111/wvn.12264
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost‐Effectiveness Analysis of Evidence‐Based Nursing Interventions to Maintain Tissue Integrity to Prevent Pressure Ulcers and Incontinence‐Associated Dermatitis

Abstract: Background: A reduction in tissue tolerance promotes the development of pressure ulcers (PUs) and incontinence-associated dermatitis (IAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 11 publications
1
31
0
5
Order By: Relevance
“…al., 2015); one used a prospective cohort design (de Laat et al, 2007), three used controlled before and after design (Avsar and Karadag, 2018, Uzun et al, 2009, and three were uncontrolled before and after design studies (Anderson et al, 2015, Rogenski and Kurcgant, 2012. Sample size varied in these studies from 78 to 399 patients with a median of 202, and interquartile range (IQR) of 170.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…al., 2015); one used a prospective cohort design (de Laat et al, 2007), three used controlled before and after design (Avsar and Karadag, 2018, Uzun et al, 2009, and three were uncontrolled before and after design studies (Anderson et al, 2015, Rogenski and Kurcgant, 2012. Sample size varied in these studies from 78 to 399 patients with a median of 202, and interquartile range (IQR) of 170.…”
Section: Resultsmentioning
confidence: 99%
“…Among the eight research studies, seven were assessed against the items for quantitative non-randomised studies of the MMAT (2018). Five of these met all five MMAT criteria (Anderson et al, 2015, Avsar and Karadag, 2018, Uzun et al, 2009, and two of studies met all but the "are the confounders accounted for in the design and analysis" criteria (Loudet et al, 2017, Rogenski andKurcgant, 2012). One study (two papers) was assessed against items for randomised trial of the MMAT , which did not meet the "are the groups comparable at baseline" criteria but met all other criteria.…”
Section: Resultsmentioning
confidence: 99%
“…2 The skin products, labour and supplies required to prevent IAD per incontinence episode incur costs that range between 0.89 and 1.31 USD. 5 IAD management is also a time-consuming practice for nurses. 5 IAD management is also a time-consuming practice for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…4 Another study reported a total cost (nursing time, product cost) between 135.68 USD and 108.77 USD per patient. 5 IAD management is also a time-consuming practice for nurses. Furthermore, IAD affects quality of life in terms of pain and itching and is a well-known risk factor for pressure ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Ülkemizde Avşar ve Karadağ'ın (2016) müdahale araştırması olarak yoğun bakım ünitelerinde doku toleransını artırmaya yönelik hemşirelik girişimlerinin doku bütünlüğüne olan etkisini inceledikleri çalışmalarında İBD oranları kontrol grubunda %31.2 (n=77); kanıta dayalı hemşirelik girişimlerinin uygulandığı müdahale grubunda %10.4 (n=77) olarak saptanmıştır. (12) İBD oluşumunda rol oynayan risk faktörlerinin bilinmesi ve doğru değerlendirme ile İBD'nin önlenmesi ve bakımının planlanması sağlanabilir. Bu durum hastalara nitelikli bakımın verilmesine olanak sağlar.…”
unclassified